Rhizomatic Criticism as a New Critical Action in Literature and Gilles Deleuze’s Rhizomatic Concept / Edebiyatta Yeni Bir Eleştirel Eylem Olarak Rizomatik Eleştiri ve Gilles Deleuze’ün Rizomatik Kavramı - Bülent Yıldız (Folklor/Edebiyat, 2022)
Deleuze, one of the most influential philosophers of the twentieth century, developed a special terminology of his own together with Guattari. The concepts they applied in this terminology have been eye-opening and guiding on many issues. Rhizome, which is borrowed from botanical science, is also one of these concepts. Rhizome, like deterritoriality, nomadic becoming or body without organs, is one of the key concepts of Deleuzean philosophy, in fact, it is the most important one. The rhizome does not grow vertically like a tree, but expands horizontally. Therefore, it has given Deleuze and Guattari a different perspective. In this sense, Rhizome has a content that breaks down the walls in front of its classical, rationalist form and enables a nomadic or deterritorialized view, and this leads the way for a different reception practice in literary criticism. The concept of Rhizomatics, which is covered with this awareness in this article, will be the intellectual key and guide for a new way of approach towards literary criticism.